Correlations of Uniaxial Compressive Strength and Modulus of Elasticity with Point Load Strength Index, Pulse Velocity and Dry Density of Limestone and Sandstone Rocks in Sulaimani Governorate, Kurdistan Region, Iraq. - Daoud, Hyam S.; Rashed, Kamal A.; Alshkane, Younis M. (Sulaimani Journal for Pure and Applied Sciences, 2017)
The Uniaxial Compressive Strength (UCS) of rocks is important parameter in design of geotechnical engineering. If the rocks are affected by weathering agents, there will be difficult to obtain intact samples and to determine UCS in laboratory.Hence, the use of another engineering index of rocks as an alternative for determining UCShave been studied and investigated by researchers. The Pulse Velocity and Point Load tests are used as a quick, easy and non-expensive means of obtaining rock strength indexes. This paper presents an experimental study for correlating between Uiaxial Compressive Strength (UCS) and Point Load Index (PLI), Pulse Velocity (Vp), Dry Density andModulus of Elasticity (E) of limestones and sandstone rock samples. 80 specimens of limestones were obtained from Pila Spi and Lower Fars Formations and 46 specimens of sandstone were obtained from Tanjero ormation. Based on the results, for the first time in this region, a new good correlation is introduced to estimate the UCS and Efrom Pulse Velocity, Point Load Index and Dry Density.
Keywords: Uniaxial compressive; Strength Point load; Index pulse velocity limestone sandstone strength correlation